Youth Financial Literacy: Pathway to Independence for SMA Bina Jaya Students - M Husni Thamrin, Kemas; Febrianti, Rahma; Mardyaningsih, Wirda; Andriana, Isni (PELITA NUSA TENGGARA, 2026)
The community service activity at SMA Bina Jaya Kertapati Palembang was successfully implemented according to the planned methods. This activity effectively encouraged active student participation through interactive discussions where students raised critical questions related to financial literacy, including effective saving methods, digital fund management via e-wallets, and strategies to resist consumptive temptations. Students demonstrated increased awareness of the importance of early financial planning and prudent digital financial management, reflecting a deeper understanding of current economic challenges. The educational approach emphasizing financial values and ethics, such as thriftiness and responsibility, proved effective in shaping healthy financial behavior. The results align with studies that highlight the positive relationship between financial literacy and economic well-being, especially among the youth. The interactive and contextualized socialization and training programs not only enhanced knowledge but also fostered positive attitudes in personal financial management to avoid consumptive behaviors. Thus, this community service contributes significantly to preparing a financially savvy generation ready to face future economic challenges.